Pengembangan Media Pembelajaran Video Animasi Berbantuan “AI” Pada Pembelajaran Bahasa Indonesia Kelas V SD Negeri 3 Talang - Deby Kartika Ratri; Nugrananda Janattaka (Journal on Education, 2024)
The development of education has made significant progress along with the changing times. Although there are many innovations today, the learning process still tends to be monotonous due to the limited variety of media that are often used. The purpose of this study is to create a more creative and interesting Indonesian learning media. Using a research and development (R&D) approach that has been modified into six initial stages, this study aims to develop learning media. Three lecturers of the Primary School Teacher Education Study Program verified the media, material, and language validation sheets as assessment instruments. This research was conducted in the fifth grade of SD Negeri 3 Talang Sendang, which consisted of eight students, involving filling out a student response questionnaire. The results showed that the learning media in the form of AI-assisted animated videos in grade V Indonesian language lessons were considered very feasible. The average value of two media experts is 88.5%, from two material experts is 86% and from two linguists 91%. The response of students also showed a very feasible category, with an average of 88.4% from the small group trial and 87.5% from the large group trial. These results confirm that AI-assisted animated videos are innovative learning media that are very suitable for use in Indonesian language lessons in grade V of SD Negeri 3 Talang Sendang.